2014
DOI: 10.1504/ijtel.2014.060022
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological methods for monitoring brain activity in serious games and virtual environments: a review

Abstract: she works as Research Assistant at the Department of Psychology (Section Neuropsychology) at the University of Graz and is involved in national and international scientific projects. Her research topics are EEG/NIRS-based brain-computer communication and neurofeedback, interacting in virtual realities, virtual reality as rehabilitation tool and spatial cognition.Elisabeth V.C. Friedrich: Dr., Postdoctoral researcher Department of Psychology, Section Neuropsychology University of Graz Universitätsplatz 2/III 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 94 publications
0
21
0
Order By: Relevance
“…79,80 Neuroimaging studies have a number of advantages over the self-reports that historically have more commonly been used in IA research. Neurobiological studies allow for an objective assessment of IA by investigating how changes in the brain may result in changes in behavior, as has been widely documented in substance-related addiction research.…”
Section: Internet Addiction and Its Associated Neuronal Processesmentioning
confidence: 99%
“…79,80 Neuroimaging studies have a number of advantages over the self-reports that historically have more commonly been used in IA research. Neurobiological studies allow for an objective assessment of IA by investigating how changes in the brain may result in changes in behavior, as has been widely documented in substance-related addiction research.…”
Section: Internet Addiction and Its Associated Neuronal Processesmentioning
confidence: 99%
“…Additionally, investigations by educational researchers about the brain of geriatric learners using low‐cost EEGs can also help dispel myths and misconceptions about geriatric individuals and their capacity to learn. One of the best support mechanisms that can be given to geriatric learners is to improve our understanding of how to best “teach an old dog new tricks.” Educational research using low‐cost neurophysiological technologies can help develop strategies to optimize cognition throughout the aging process and for evaluating the effectiveness of these strategies (Ninaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best support mechanisms that can be given to geriatric learners is to improve our understanding of how to best "teach an old dog new tricks." Educational research using low-cost neurophysiological technologies can help develop strategies to optimize cognition throughout the aging process and for evaluating the effectiveness of these strategies (Ninaus et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroencephalography (EEG) and functional near‐infrared spectroscopy (fNIRS) have also been used to monitor brain activities associated with video game playing . It has been demonstrated that it is feasible to use EEG to explore event‐related neural processes during video game playing under naturalistic conditions .…”
Section: Introductionmentioning
confidence: 99%